Mapping Loneliness in Australia - Flood, M (My University, 2005)
This paper maps loneliness in Australia. Using national survey data, it outlines patterns of loneliness, support and friendship and assesses who is most at risk of emotional and social isolation and who is socially supported and connected. The paper focuses on young adults aged 25 to 44, a demographic that has been neglected in existing studies of loneliness despite the fact that solitary living has shown the most significant increase among such people.
The Australia Institute, Discussion Paper
Keywords: Social Capital -- Social support; Social Capital; Social engagement; Social Engagement